2010
DOI: 10.1039/c003342a
|View full text |Cite
|
Sign up to set email alerts
|

Geobacter sulfurreducens biofilms developed under different growth conditions on glassy carbon electrodes: insights using cyclic voltammetry

Abstract: Growth of biofilms of G. sulfurreducens on glassy carbon that yield a bioelectrocatalytic response to acetate oxidation is achieved using a fixed applied potential, with current density for acetate oxidation scaling with applied potential. In contrast biofilms grown under electron acceptor-limiting conditions display redox signals shifted to lower potentials and do not oxidise acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
124
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 16 publications
26
124
0
Order By: Relevance
“…Another aspect of anaerobic hydrocarbon degradation of importance to energy concerns is the potential for some microorganisms to anaerobically oxidize components of hydrocarbon deposits, degrading the quality of the reservoir. It is generally considered that the heating of deposits to [80][81][82][83][84][85][86][87][88][89][90] C associated with deep burial kills hydrocarbon-degrading microorganisms, sterilizing the deposits. 108 However, it was recently found that Ferroglobus placidus anaerobically oxidizes a diversity of straight-chain and branched alkanes, as well as aromatic hydrocarbons with the reduction of Fe(III) at temperatures as high as 94 C. 109,110 Therefore, further investigation of the mechanisms controlling microbial degradation of petroleum hydrocarbon deposits is warranted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of anaerobic hydrocarbon degradation of importance to energy concerns is the potential for some microorganisms to anaerobically oxidize components of hydrocarbon deposits, degrading the quality of the reservoir. It is generally considered that the heating of deposits to [80][81][82][83][84][85][86][87][88][89][90] C associated with deep burial kills hydrocarbon-degrading microorganisms, sterilizing the deposits. 108 However, it was recently found that Ferroglobus placidus anaerobically oxidizes a diversity of straight-chain and branched alkanes, as well as aromatic hydrocarbons with the reduction of Fe(III) at temperatures as high as 94 C. 109,110 Therefore, further investigation of the mechanisms controlling microbial degradation of petroleum hydrocarbon deposits is warranted.…”
mentioning
confidence: 99%
“…2) and possibly other outer surface c-type cytochromes. 74,[76][77][78]84,85 OmcZ is a multi-heme cytochrome, 86 which is not required for Fe (III) oxide reduction, 60 but is highly expressed in currentproducing biofilms and is required for optimal current production. 60,75 Immunogold labeling studies have revealed that OmcZ is located outside the cell and in electrode biofilms OmcZ accumulates at the biofilm-electrode interface.…”
mentioning
confidence: 99%
“…Fe(III) oxide) electron acceptors for respiration 1 . In the absence of an alternative electron acceptor G. sulfurreducens has been shown to form thick electron-conducting biofilms (>50 µm) on an adequately polarised solid electrode surface (anode) which can act as an artificial, inexhaustible, electron sink 2,3 . Our previous work examining the charge transfer properties of G. sulfurreducens biofilms, grown under controlled applied potentials, has shown that biocatalytic current, generated from oxidation of acetate, scales with applied potential 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of an alternative electron acceptor G. sulfurreducens has been shown to form thick electron-conducting biofilms (>50 µm) on an adequately polarised solid electrode surface (anode) which can act as an artificial, inexhaustible, electron sink 2,3 . Our previous work examining the charge transfer properties of G. sulfurreducens biofilms, grown under controlled applied potentials, has shown that biocatalytic current, generated from oxidation of acetate, scales with applied potential 3 . The acetate oxidation currents do not scale directly to biofilm thickness 4 , however, suggesting that either mass or charge transport limits the overall current or that the biofilm formed over time displays differences in bacterial cell densities, viability and/or redox response.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the lower current density produced by G. sulfurreducens at higher potential could be suggested to be similar discovered for S. oneidensis, where lower current density was attributed to increased protein degradation caused by the high electrode potential [99]. Cyclic voltammograms were recorded under turnover conditions once the A and B respectively) are representative of those typically seen for Geobacter [177][178][179].…”
Section: Resultsmentioning
confidence: 99%